2018
DOI: 10.3390/molecules23102492
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Cd in Soil Using Laser-Induced Breakdown Spectroscopy in Air and Ar Conditions

Abstract: Rapid detection of Cd content in soil is beneficial to the prevention of soil heavy metal pollution. In this study, we aimed at exploring the rapid quantitative detection ability of laser- induced breakdown spectroscopy (LIBS) under the conditions of air and Ar for Cd in soil, and finding a fast and accurate method for quantitative detection of heavy metal elements in soil. Spectral intensity of Cd and system performance under air and Ar conditions were analyzed and compared. The univariate model and multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…The CARS-PLS algorithm was applied to select characteristics variables from the spectra. 25 Running times were 50 and 8 times those used by the interactive validation model. The best model was chosen according to the lowest RMSEP value.…”
Section: Results Obtained With the Cars-pls Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The CARS-PLS algorithm was applied to select characteristics variables from the spectra. 25 Running times were 50 and 8 times those used by the interactive validation model. The best model was chosen according to the lowest RMSEP value.…”
Section: Results Obtained With the Cars-pls Modelmentioning
confidence: 99%
“…23 It is based on Darwin's evolution theory and used for the selection of N subsets of variables by conducting N sampling runs iteratively. 24,25 RF is an efficient method that borrows the framework from the reversible-jump Markov chain Monte Carlo method. 26 The RF algorithm served as a selection of variables based on normal distribution, and the variables were added or deleted, making a foundation for model building.…”
Section: Data Analysis Using Chemometric Algorithmsmentioning
confidence: 99%
“…The results showed that the LS-SVR model under an Ar atmosphere obtained the best performance. The root-mean-square error for calibration (RMSEC) and the root-mean square error for prediction (RMSEP) were only 0.026 and 0.034, respectively, which demonstrated the ability of LIBS for the accurate quantitative detection of Cd in soil [21]. To the best of our knowledge, the simultaneous quantitative detection of N, P, and K elements based on LIBS coupled with SVR models by different parameter optimization methods has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the LS-SVM model for an Ar environment provided the best performance of prediction with R 2 of 0.98, and root mean square error of prediction (RMSEP) of 0.034 mg kg -1 . The authors concluded that LIBS combined with LS-SVM for anAr environment condition could be a useful tool for the accurate prediction of Cd for environmental monitoring(94).Table 1summarizes some of the available studies on the application LIBS for predicting PTEs in the soils. Compared with XRFS, few papers are available reporting results obtained by LIBS.…”
mentioning
confidence: 99%
“…Compared with XRFS, few papers are available reporting results obtained by LIBS. The use of multivariate statistical analyses is still limited to the commonly used PLSR, with a very limited application of machine learning methods(94). Spectral data preprocessing is not regularly applied, although standard normal variate (SNV) and wavelet methods are used to correct the spectral information, and reduce noise in order to improve the prediction performance(89).…”
mentioning
confidence: 99%